THE ROLE OF CLIMATE FACTORS IN THE FORMATION OF ANCIENT ERSHI CITY (Scientific journal of the Fergana State University, 2025)
This article discusses the climate and hydrological factors that influenced the formation and development of the ancient city of Ershi, specifically in the region of the Mingtepa historical monument in the Marhamat district of Andijan province. The natural and geographical advantages and opportunities that distinguish Ershi, located in the southeastern part of the Fergana Valley, in the lowland of Oyim-Khojaobod-Marhamat, from other areas of the valley are examined.